THE INFLUENCE OF INDONESIA'S REALISTIC MATHEMATICS EDUCATION APPROACH ON STUDENTS' CREATIVE THINKING ABILITY - Syutaridho, Syutaridho; Ramury, Feli; Nurhijah, Nurhijah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This research aims to explore how PMRI, a student-centered and contextualized mathematics learning approach, can foster students' creative thinking abilities in the morning, when students may have different levels of alertness, motivation, and mood, which are the result of applied science, in the field of mathematics education. The research method used is a quantitative method with Posttest-Only Control Design. The population of this study was class VIII students. The sample used was 2 classes with a quota sampling technique where classes determined from the school were used as samples. The data collection techniques used are tests and observations. Based on the student test results, a significance value of 0.00 was obtained, which means a value of 0.00 < 0.05. Observations are carried out to see the implementation of learning. Based on the results of observations, the learning carried out was following PMRI characteristics, which means the learning was carried out well. From the research results, it was concluded that using the Indonesian realistic mathematics education approach in the morning influenced the creative thinking abilities of class VIII students at Lais State Middle School. The novelty of this research is that it introduces a new experiment of PMRI learning in the morning on students' creative thinking abilities. The research contributes to the literature on mathematics education and creative thinking by highlighting the role of PMRI in improving students' creative thinking abilities in the morning.